كفاءة التنظيم الإداري لدى مديري المدارس الثانويه العامة بليبيا- دراسة ميدانية - Naser Muftah Ayad Zarzah (Universiti Sains Islam Malaysia, 2024)
This study aimed to identify the efficiency level of administrative regulation with its elements job division, administrative sequence, organizational building, business coordination for managers in general secondary schools in Tripoli and identifying the impact of each of the variables school volume, gender, experience, academic qualifications, number of training courses on the efficiency level of administrative regulation by the managers the general secondary schools in Tripoli, and identifying the effect of using the modern methods on the efficiency level of administrative regulation by the managers the general secondary schools in Tripoli. It also aimed to identify the main difficulties facing the managers in these schools during their administrative job, the researcher has used the descriptive and analytical methodology. The study sample composed of 787 teachers and 91 School manager. The researcher used questionnaire as the main method for collecting data. The questionnaire has been design in two copies, one copy for teachers and the second copy for school managers, total items of questionnaire equal to 84 distributed on the main study axis which is the axis of regulation element which include: (job division, administrative sequence, organizational building, business coordination), and the axis of using the modern methods, and the axis of difficulties. The study showed there were a significant differences and statistic indicator between the managers and teachers perspective about the efficiency levels of administrative regulation in these schools through the above mentioned elements and for the managers. It also revealed the absence of any moral effect with statistic indication on the school volume, gender, academic qualification, and participating in training courses about the level of efficiency of administrative regulation by managers of the general secondary schools in Tripoli. This study recognized that no contrast exist between the two perspective of managers and teachers about impact of experience on the efficiency level of administrative regulation by managers, and according to the opinions of managers, it showed that the moral indicator was not exist and statistically indicating the experience on the level of administrative regulation by the managers of the general secondary schools in Tripoli, whereas the teachers opinion showed there was a moral effect that was statically indicating the experience on the level of efficiency of administrative regulation by the managers.